Phalarodon fraasi Merriam 1910 - Roberts, Aubrey Jane; Engelschiøn, Victoria Sjøholt; Hurum, Jørn Harald (Zenodo, 2022)
Phalarodon fraasi Merriam, 1910 Figs. 1–3. Diagnosis .—Modified from Merriam (1910) and Ji et al. (2015). Marginal teeth ankylosed; significant heterodonty between anterior and posterior teeth in the maxilla; dental groove absent anteriorly and posteriorly (not clear in premaxilla of PMO 235.393); number of primary digits in forelimb increased to six; six distal carpals; metatarsal III gives rise to two digits. Material .— PMO 235.393, skull, mandible and some axial and appendicular elements, the Isfjorden area (Spitsbergen), Middle Triassic. Description .—The skull, mandible and some axial and appendicular elements are present. Using CT, it is possible to see that the skull is slightly distorted, with the right side positioned lower than the left side (Fig. 2). Ontogeny is not possible to determine as no bone surface is preserved. However, based on the size of the specimen and the relative size of the orbit, it is thought to be osteologically mature (Fernández et al. 2005). No braincase or palatal elements are visible for description on the specimen or by using CT. PMO 235.393 is referred to Mixosauridae based on the long sagittal crest which reaches the nasal; the large anterior terrace of the upper temporal fenestra; and posterior teeth more robust than anterior teeth. The specimen is referred to Phalarodon based on the presence of significant heterodonty a labial mandibular shelf and the lack of a dental groove in the maxillary region (Ji et al. 2015). Skull: Premaxilla : Part of the premaxilla is damaged and missing on the left side. Using the CT scan, the right can be described in more detail. No over- or underbite is visible; however, the rostral tip is enclosed in matrix on slab D (SOM: fig. S4). Numerous teeth are set in the element (see dentition). The dentition cannot be clearly defined due to poor contrast, but there is some indication of ankylosed thecodonty (Fig. 3). This is likely a resolution and/or preservation issue, as the three-dimensional Phalarodon fraasi premaxilla (PMO 210.122) described ...